2007
DOI: 10.1002/jat.1242
|View full text |Cite
|
Sign up to set email alerts
|

Citrinin and endosulfan induced maternal toxicity in pregnant Wistar rats: pathomorphological study

Abstract: Dietary exposures to environmental food pollutants such as mycotoxin(s) or pesticide(s) have gained immense significance due to their adverse effects on production and reproduction in animal and human populations. The present investigation was conducted to evaluate the maternal toxicity of citrinin (CIT) and endosulfan administered per os either alone or in combination in pregnant rats during gestational days 6-20. CIT (group I, 10 mg kg(-1) feed, through diet) and endosulfan (group II, 1 mg kg(-1) body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 16 publications
(12 reference statements)
4
23
0
1
Order By: Relevance
“…20% of women dropped out of the study essentially for breast tenderness, weight increase, spotting and nausea during continued 10 cycles use of a new triphasic oral contraceptive (WL-49(50) 'Trinordiol') containing the lowest quantity of steroids in 75 healthy teenager young women. Singh ND et al, recorded [24] vascular changes and hemosiderosis in uterus associated with lymphocytic depletion and apoptosis in the lymphoid organs in induced toxic Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…20% of women dropped out of the study essentially for breast tenderness, weight increase, spotting and nausea during continued 10 cycles use of a new triphasic oral contraceptive (WL-49(50) 'Trinordiol') containing the lowest quantity of steroids in 75 healthy teenager young women. Singh ND et al, recorded [24] vascular changes and hemosiderosis in uterus associated with lymphocytic depletion and apoptosis in the lymphoid organs in induced toxic Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding on reduction weight are consistent are with previous reports. 18,19 The study further revealed OTA-induced normocytic hypochromic anemia. There was also reduction in total leukocyte count marked by lymphocytopenia along with increase in neutrophil percentage.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of the mycotoxin citrinin on inhibiting the maturation of oocytes, fertilization efficiency and fetal development have been investigated (Chan and Shiao, 2007;Chan, 2008). Moreover, citrinin plays a potent role in inducing maternal toxicity (Singh et al, 2007b) and teratogenic effects in Wistar rats (Singh et al, 2007a). This is similar to its toxic effect on the male reproductive system, increasing the number of abnormal spermatozoa and decreasing the number of live spermatozoa (Qingqing et al, 2012).…”
Section: Effect Of Red Monascal Rice Supplementation On Fish Reproducmentioning
confidence: 99%
“…produces up to 2.5 g kg -1 citrinin, while liquid culture has reached as high as 56 mg kg -1 (Eisenbrand, 2006). This compound has been found to induce reproductive abnor-malities in male gametes (Qingqing et al, 2012), and to reduce the rate of oocyte maturation and fertilization (Chan, 2008); it also has a teratogenic effect (Chan and Shiao, 2007;Singh et al, 2007a;Chan, 2008), and has induced maternal toxicity in pregnant rats (Singh et al, 2007b). Moreover, it has been associated with cytoto-xicity (Liu et al, 2005) and the activation of apoptosis by the mitochondrial pathway (Yu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%